Pengembangan Media Pembelajaran Monopoli pada Materi Fungsi Bagian Tubuh Hewan dan Tumbuhan di Kelas Bagi Siswa Kelas 4 SD - Wulan Suci Rimadhani; Karimatus Saidah; Muhamad Basori (Journal on Education, 2023)
The problems of this research are 1) What is the validity of Monopoly learning media on the function material of animal and plant body parts for fourth grade students of Sanggrahan 2 Prambon Nganjuk Elementary School 2) What is the practicality of Monopoly learning media on material function of animal and plant body parts for fourth grade students of Sanggrahan 2 Prambon Nganjuk Elementary School 3) How is the effectiveness of Monopoly learning media on material function of animal and plant body parts for Grade IV students at SDN Sanggrahan 2 Prambon Nganjuk This research is a type of development research with reference to research and development. According to Robert Maribe Branch (2009) in Sugiyono (2015: 38) "ADDIE is an extension of Analysis, Design, Development, Implementation and Evaluation". Research data collection techniques through observation, material expert validation questionnaires and expert validation questionnaires. media, teacher response questionnaire, student response questionnaire, pre-test and post-test. the implementation of monopoly learning media was carried out in trials, research trials were carried out at SDN Sanggrahan 2 Prambon. The results of Monopoly learning media research on the function of animal and plant body parts for fourth grade students at Sanggrahan 2 Prambon Elementary School conducted a validity test by media and material experts, the material validation test was carried out in 2 stages. . the second validation test with a score of 97% means that it is in the Very Valid criteria. for the results of the validation test by the learning media, 2 stages were carried out, the first was the validation test by the media with a score of 86.25%, meaning that it was included in the Very Valid criteria, the second was the validation test by the media with a score of 88.75%. the practicality test was validated by teachers and students, the results of the practicality test by the Teacher Response Questionnaire obtained a score of 77.78%, which means that it is included in the practical criteria and is easy to use. The results of the effectiveness test were carried out with the pretest and post-test, stated to be Very Effective in increasing students' ability to investigate the function of animal and plant body parts. Evidenced by the achievement of KKM ≥70 questions Posttest 100% of students who are able to achieve KKM.